2008
DOI: 10.1088/1748-9326/3/2/025009
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of water uptake by soot particles

Abstract: Quantification of atmospheric processes including the water uptake by soot particles of various origin, emitted from different sources, requires identification of hydrophobic and hydrophilic soot. Water uptake measurements are performed on well-characterized laboratory soots available for atmospheric studies. Comparative analysis of water adsorption isotherms on soots of various compositions allows us to suggest a concept of quantification. Systematic analysis demonstrates two mechanisms of water/soot interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 67 publications
8
83
1
Order By: Relevance
“…This results in the soot acting as poor CCN with activated fractions of 0%-30% and κ ∼ 10 −3 . We note that this differs from the findings of Popovicheva et al (2008), who found aircraft engine soot to be hygroscopic in the sense Kerminen et al (1997) Kroll et al (2012), and u Petzold et al (2005).…”
Section: Comparison To Aircraft and Diesel Soot Sourcescontrasting
confidence: 99%
See 2 more Smart Citations
“…This results in the soot acting as poor CCN with activated fractions of 0%-30% and κ ∼ 10 −3 . We note that this differs from the findings of Popovicheva et al (2008), who found aircraft engine soot to be hygroscopic in the sense Kerminen et al (1997) Kroll et al (2012), and u Petzold et al (2005).…”
Section: Comparison To Aircraft and Diesel Soot Sourcescontrasting
confidence: 99%
“…Popovicheva et al (2008) used a gravimetric method to measure sub-saturated water uptake on CAST burner soot at two conditions: flame C/O ratio of 0.29 (4% OC) and 0.4 (27% OC), which are the same conditions examined by Möhler et al (2005). They find that more monolayers of water adsorb on the surface of the higher-OC soot than the lower-OC soot, which leads them to classify the former soot as hydrophilic and the latter soot as hydrophobic.…”
Section: Soot Hygroscopicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiplying the BET value by the soot concentration yields a total surface concentration of [PS] g =5×10 −5 cm 2 cm −3 . However, BET values for soot can range from 6 m 2 g −1 for aircraft engine combustor soot (Popovicheva et al, 2008) to approximately 500 m 2 g −1 for the post-treated black carbon Degussa FW2 (Dymarska et al, 2006), which can lead to large differences in [PS] g . Thus, the implemented BET-value of 500 m 2 g −1 may result in an upper limit for the concentration of surface reaction sites.…”
Section: Representation Of Sootmentioning
confidence: 99%
“…Two mechanisms of water/soot interaction have been proposed: bulk dissolution into water-soluble coverage (hygroscopic soot) and the water molecule adsorption onto surface oxygen-containing functionalities (non-hygroscopic soot) (Popovicheva et al, 2008b). The formation of a water film extended over the surface separates hydrophobic from hydrophilic soot.…”
Section: Introductionmentioning
confidence: 99%